2019
DOI: 10.4055/cios.2019.11.3.258
|View full text |Cite
|
Sign up to set email alerts
|

Pearls and Tips in Shoulder Arthroplasty

Abstract: There has been rapid evolution in new techniques and technology in shoulder arthroplasty. This has improved the efficiency of the procedures as well as expanded our ability to manage some of the most challenging cases. This article will review key aspects of patient evaluation, discuss key technical steps in primary anatomic and reverse arthroplasty, and lastly provide tips to facilitate revision surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Many surgical procedures have been introduced for the treatment of irreparable RCTs: arthroscopic debridement, 27 tuberoplasty, 16 , 54 partial repair, 3 interposition grafting (IG), 41 , 46 superior capsular reconstruction (SCR), 34 tendon transfers, 15 , 17 reverse total shoulder arthroplasty, 6 , 39 , 50 and arthrodesis. 11 Among these surgical procedures, IG and SCR are 2 of the most commonly performed.…”
mentioning
confidence: 99%
“…Many surgical procedures have been introduced for the treatment of irreparable RCTs: arthroscopic debridement, 27 tuberoplasty, 16 , 54 partial repair, 3 interposition grafting (IG), 41 , 46 superior capsular reconstruction (SCR), 34 tendon transfers, 15 , 17 reverse total shoulder arthroplasty, 6 , 39 , 50 and arthrodesis. 11 Among these surgical procedures, IG and SCR are 2 of the most commonly performed.…”
mentioning
confidence: 99%
“…RTSA has been shown to have efficacy for the treatment of debilitating shoulder diseases with rotator cuff deficiency[ 4 , 9 ]. As the indications for RTSA have expanded, there has been a dramatic growth in the frequency of RTSA worldwide over the past decade[ 3 , 10 ]. In the past, bilateral RTSA was considered inadvisable because patients may struggle with ADLs following treatment[ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similar to RDA of the hip, RDA of the shoulder may not respond well to conservative treatment. In a review of the literature, all reported cases with RDA due to SIF of the shoulder underwent arthroplasty [17]. Our cases were treated by shoulder arthroplasty (n = 17) or arthroscopic debridement (n = 3) depending on the patient's age, activity, symptoms, degree of head destruction, and presence or absence of a rotator cuff tear [18,19].…”
Section: Discussionmentioning
confidence: 99%